Strategi Efektif dalam Mengelola Opini Publik di Era Media Digital: Tantangan dan Peluang Bagi Institusi dan Individu - Surahmat, Surahmat; Muarih Adaby, Achmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In the digital media era, managing public opinion has become a significant challenge for institutions and individuals. Information that circulates rapidly, whether accurate or misleading, can greatly impact public perception. This research aims to identify effective strategies for managing public opinion, including rapid response, information verification, two-way interaction, and the use of sentiment analysis technology. The findings reveal that institutions utilizing digital technology can more efficiently monitor and manage public opinion. Additionally, data security is a crucial element in maintaining public trust. By implementing strict data security policies and enhancing digital literacy among the public, institutions can mitigate misinformation risks and protect their reputations. In conclusion, effective public opinion management in the digital era requires a multidimensional approach involving proactive communication, technology, and robust security policies.